2020
DOI: 10.3390/catal10070757
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Strategies for Enhancing the Performance of Co3O4/Al2O3 Catalysts for Lean Methane Combustion

Abstract: Spinel-type cobalt oxide is a highly active catalyst for oxidation reactions owing to its remarkable redox properties, although it generally exhibits poor mechanical, textural and structural properties. Supporting this material on a porous alumina can significantly improve these characteristics. However, the strong cobalt–alumina interaction leads to the formation of inactive cobalt aluminate, which limits the activity of the resulting catalysts. In this work, three different strategies for enhancing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…In light of the above aspects, the present Special Issue is mainly focused on the fabrication and fine-tuning of NMs-free metal oxide catalysts by means of advanced synthetic and/or promotional routes. It consists of fourteen high quality papers, involving: a comprehensive review article on the recent advances on the rational design and fine-tuning of ceria-based metal oxide catalysts [5]; two articles on the ceria nanoparticles morphological effects on N 2 O decomposition [14] and CO oxidation [10] over ceria-based binary oxides; two articles on NO decomposition over K-promoted Co-Mn-Al mixed oxides [34,35]; one article on the effect of ceria synthesis methods on the carbon pathways in dry reforming of methane (DRM) over Ni/CeO 2 catalysts [36]; one article on the impact of synthesis procedure and aliovalent doping in Co-Al spinel-type oxides for lean methane combustion [37]; one article on the support effect on the direct conversion of syngas to higher alcohols over copper-based oxides [38]; one article on nanofibrous Ni/Al 2 O 3 catalysts prepared by electrospinning for methane partial oxidation [39]; one article on the influence of precursor compounds on the selective catalytic reduction (SCR) of NO x by NH 3 over FeMgO x oxides [40]; one article on the synthesis and active sites determination of ZrO 2 -supported WO x solid acid catalysts [41]; one article on the synthesis and electrocatalytic performance of RuO 2 nanoparticles [42]; one article on the fabrication and photocatalytic performance of mesoporous frameworks of ZnFe 2 O 4 (ZFO) and MnFe 2 O 4 (MFO) nanoparticles [43]; and one article on the synthesis of polymer supported catalysts for arylamination reaction [44].…”
Section: This Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…In light of the above aspects, the present Special Issue is mainly focused on the fabrication and fine-tuning of NMs-free metal oxide catalysts by means of advanced synthetic and/or promotional routes. It consists of fourteen high quality papers, involving: a comprehensive review article on the recent advances on the rational design and fine-tuning of ceria-based metal oxide catalysts [5]; two articles on the ceria nanoparticles morphological effects on N 2 O decomposition [14] and CO oxidation [10] over ceria-based binary oxides; two articles on NO decomposition over K-promoted Co-Mn-Al mixed oxides [34,35]; one article on the effect of ceria synthesis methods on the carbon pathways in dry reforming of methane (DRM) over Ni/CeO 2 catalysts [36]; one article on the impact of synthesis procedure and aliovalent doping in Co-Al spinel-type oxides for lean methane combustion [37]; one article on the support effect on the direct conversion of syngas to higher alcohols over copper-based oxides [38]; one article on nanofibrous Ni/Al 2 O 3 catalysts prepared by electrospinning for methane partial oxidation [39]; one article on the influence of precursor compounds on the selective catalytic reduction (SCR) of NO x by NH 3 over FeMgO x oxides [40]; one article on the synthesis and active sites determination of ZrO 2 -supported WO x solid acid catalysts [41]; one article on the synthesis and electrocatalytic performance of RuO 2 nanoparticles [42]; one article on the fabrication and photocatalytic performance of mesoporous frameworks of ZnFe 2 O 4 (ZFO) and MnFe 2 O 4 (MFO) nanoparticles [43]; and one article on the synthesis of polymer supported catalysts for arylamination reaction [44].…”
Section: This Special Issuementioning
confidence: 99%
“…The impact of different synthetic/modification routes towards enhancing the lean methane combustion of Co 3 O 4 /Al 2 O 3 spinel-type oxides was investigated by Rubén López-Fonseca and co-workers [37]. Three different strategies for enhancing the performance of alumina-supported catalysts were examined: (i) surface protection of the alumina with magnesia prior to the deposition of the cobalt precursor, (ii) coprecipitation of cobalt along with nickel and (iii) surface protection of alumina with ceria.…”
Section: Contribution Highlightsmentioning
confidence: 99%
“…In a search for a Pt-group-metal-free methane combustion catalyst for applications in exhaust aftertreament of natural gas vehicles, cobalt oxide-containing materials attract the most interest because of their ability to activate and oxidize methane, as well as their lower price and higher abundance as compared to the conventionally used platinum group metal (PGM) catalysts. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] For stoichiometric engines, CoO x may increase the operational window of air-to-fuel ratio (lambda) by supplying its lattice oxygen for complete combustion. [4] For CH 4lean feeds, the oxide is active at relatively low temperatures with the combustion activation energies in the range of 60-80 kJ/mol.…”
Section: Introductionmentioning
confidence: 99%
“…In view of such promising combustion properties but insufficient amount of active sites and sintering of the pure Co 3 O 4 catalyst, in this work, we aimed to address the former two disadvantages by cobalt deposition on a solid support, which is a typical strategy in heterogeneous catalyst preparation for an increased dispersion and stability. Choya et al [2] [6] The Co/Al 2 O 3 -CeO 2 catalyst demonstrated the improved performance as compared to the Ce-free sample in the first three light-off methane combustion reactions; the effectiveness of ceria in preventing the CoAl 2 O 4 formation in the long term was not reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation